The alternative to progress: developmental nationalism, his intelectuals and educational planning in the 1960s in Brazil - Santos, Lincoln de Araújo (2019)
The beginning of developmentalism as a political project and its influences in our social and educational thinking brought together in the 1960s intellectuals committed and articulated with this ideology. In the set of political and social crisis, Celso Furtado, Darcy Ribeiro, Anísio Teixeira and Paulo Freire thought Brazil based on convergence of ideas that brought them closer to development-nationalism. Analysis of documentary sources identifies, in the narratives, the ideals of a national development project that highlights the National Plan and the Triennial Plan of Education.